Analisis Efektivitas, Efesiensi Dan Kontribusi Penerimaan Pajak Daerah Terhadap Pendapatan Asli Daerah Tahun 2010-2016 - Endi Rustendi (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2018)
This research aims to determine the level of effectiveness of regional tax revenues in Bekasi Regency in 2010-2016, to determine the level of efficiency of regional tax revenues in Bekasi Regency in 2010-2016, to determine the contribution of regional tax revenues to Bekasi District's Original Revenue in 2010-2016. This research is descriptive research, descriptive method in this study is used to describe the regional tax revenue and quantitative analysis of regional tax revenue in Bekasi Regency which consists of efficiency (efficiency), effectiveness (effectivity) and its contribution to the original revenue of Bekasi Regency in 2010 to with 2016. The technique of collecting data by interview, documentation study, while descriptive analysis is used to obtain an overview of regional tax revenues and local revenue, while quantitative analysis in calculating the tax formula is used to determine the regional tax revenue managed by the Regional Revenue Service of Bekasi Regency budget year 2010 to 2016.The results of the calculation of effectiveness are done by comparing the realization of regional tax collection with the potential / target of regional taxes. Based on these results, the effectiveness of Bekasi Regency Regional Tax revenues in 2010 up to 2016 shows an average percentage of 114.28% with a very effective category. The level of efficiency of Regional tax revenues in 2010-2016 in Bekasi Regency by comparing the costs of collection with the realization of Regional taxes. From this calculation, it can be seen in 2010 to 2016 showing the average percentage of 44.51% with the category quite efficient. Contribution of Regional tax revenue in 2010-2016 in Bekasi Regency by comparing the realization of Regional tax with local revenue. From this calculation, it can be seen from 2010 to 2016 showing the average percentage of 0.74% with very less categories.